En el filo de la navaja de las dicotomías fantásticas: Identidad virtual y fantasmas de la aldea global en Martín Felipe Castagnet y Samanta Schweblin (Altre Modernità, 2022)
Contemporary texts falling under the label of the fantastic share a tendency to employ images and metaphors referring to the globalization processes, as well as to break the canonical rules of the genre. In this paper, I will focus my attention on the notion of individual identity by comparing Los cuerpos del verano by Martín Felipe Castagnet and Kentukis by Samanta Schweblin. My aim is to underline the blurring of the frontiers between the opposites of two fundamental couples of concepts in the theory of the fantastic: body vs. mind, and real vs. virtual.
Keywords: fantastic; mind; body; virtual; identity; global